2013
DOI: 10.3349/ymj.2013.54.4.888
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Oncologic Outcomes in Locally Advanced Gastric Cancer with Neoadjuvant Chemotherapy or Chemoradiotherapy

Abstract: PurposeAlthough neoadjuvant therapy has been accepted as a treatment option in locally-advanced gastric cancer, its prognostic value has been difficult to evaluate.Materials and MethodsSeventy-four gastric cancer patients who underwent gastrectomy after neoadjuvant treatment were divided into two groups according to the pathologic response: favorable (ypT0) and others (ypT1-4). The clinicopathologic characteristics, predictive factors for pathologic response, and oncologic outcome were evaluated.ResultsEleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…However, it is showed that PNI is an independent pathway of metastasis because the perineural space is different from the lymphatic canal in anatomical and microstructural aspects. In our study it is showed that the positive rate of PNI was closely related to the invasion of blood vessels and lymphatic vessels, which may be one of the reasons for the high incidence of PNI [7].…”
Section: Discussionmentioning
confidence: 57%
“…However, it is showed that PNI is an independent pathway of metastasis because the perineural space is different from the lymphatic canal in anatomical and microstructural aspects. In our study it is showed that the positive rate of PNI was closely related to the invasion of blood vessels and lymphatic vessels, which may be one of the reasons for the high incidence of PNI [7].…”
Section: Discussionmentioning
confidence: 57%
“…In recent years, a multidisciplinary treatment approach including preoperative chemotherapy, radiotherapy, and target therapy has emerged for advanced or metastatic GC, resulting in increased curability and improved survival 14 . Recent studies have suggested that neoadjuvant chemotherapy in patients with locally advanced or metastatic GC can enable curative resection and improve survival [15,16]. In our previous study, we observed that survival and quality of life of patients with locally advanced or metastatic GC who received neoadjuvant chemotherapy were superior to those of patients who received only supportive care [2,3].…”
Section: Discussionmentioning
confidence: 79%
“…GC remains a leading malignancy worldwide, and management of patients with locally advanced or metastatic GC has not substantially changed in the last few decades. A neoadjuvant strategy may increase the likelihood of completing multimodality therapy, particularly when surgical management is associated with significant morbidity and complications that may preclude timely adjuvant therapy [9][10][11][12][13][14][15]. Preoperative concurrent chemoradiotherapy (CCRT) is a well-established primary treatment modality in other gastrointestinal malignancies including esophageal [9,11] and rectal cancer [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…GC remains a leading malignancy worldwide, and management of patients with locally advanced or metastatic GC has not substantially changed in the last few decades. A neoadjuvant strategy may increase the likelihood of completing multimodality therapy, particularly when surgical management is associated with significant morbidity and complications that may preclude timely adjuvant therapy [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%